Profiling of peripheral T-cell lymphomas in Kerala, South India: A 5-year study - Rekha A Nair; Jayasudha Arundhathi Vasudevan; Priya Mary Jacob; Renu Sukumaran (Wolters Kluwer Medknow Publications, 2017)
Background: Peripheral T-cell lymphomas (PTCLs) are non-Hodgkin's lymphomas (NHLs) with considerable variation in incidence across the world. They show a wide variety of clinicopathological features and generally associated with poor clinical outcome. Lymphoma data from different geographic regions will definitely aid in routine clinical practice and research work. PTCLs are reported with a higher frequency in Asia as compared to Western countries. Objective: The objective of this study was to analyze the frequency and distribution of PTCLs diagnosed in a tertiary care cancer center in Kerala. Materials and Methods: This was a retrospective study carried out in the Division of Pathology, Regional Cancer Centre, Thiruvananthapuram, for 5 years from January 1, 2011, to December 31, 2015. All PTCLs diagnosed during this period were reviewed and then classified according to the 2016 revision of the World Health Organization classification of lymphoid neoplasms. Statistical significance of the results was evaluated using Chi-square test. Results: Among the total 3108 cases of lymphomas diagnosed at our center, 2404 cases were NHLs (77.35%). PTCLs (n = 333) contributed 13.85% of all NHLs. Among these, PTCL, not otherwise specified, constituted the most common subtype (92 cases, 27.63%), followed by angioimmunoblastic T-cell lymphoma (79 cases, 23.72%), anaplastic large cell lymphoma (75 cases, 22.52%), mycosis fungoides (28 cases, 8.40%), and adult T-cell leukemia/lymphoma (ATLL) (28 cases, 8.40%). Conclusion: This is the largest study on PTCLs reported from Kerala. We document that the frequency of PTCLs is higher than that reported from Western studies. The frequency of ATLL reported from Kerala is much higher than that reported from other states.